Mobile Robot Navigation in Dynamic Environments Using an Improved RRT* Approach - Mohammed, Hussein Ali (2018)
A Master of Science thesis in Mechatronics Engineering by Hussein Ali Mohammed entitled, “Mobile Robot Navigation in Dynamic Environments Using an Improved RRT* Approach”, submitted in November 2018. Thesis advisor is Dr. Lotfi Romdhane and thesis co-advisor is Dr. Mohammad Jaradat. Soft and hard copy available.